Intervention Motion Program Of Rhythmic Gymnastics And Its Impact On The Development Of Motor Abilities - Barbora Novotna; Michaela Slovakova (European Scientific Journal, ESJ, 2016)
The aim of this study is to present the research results of intervention motion program with rhythmic gymnastics´ content on chosen motor abilities of early school age pupils. The program was performed in school within the educational process of physical education. The experiment was realized with selected pupils in the 4th classes at primary schools in Banská Bystrica. The evaluation of motor abilities was realized. Thanks to the chosen standardized tests. The content analysis of motor tests´ results show a significant (p < 0.01) impact of applied motion program on the level of chosen coordination abilities of pupils with recommendation to the school practice.